Spatial scale influences how people value and perceive green open space - Ives, Christopher D.; Gordon, Ascelin; Oke, Cathy; Raymond, Christopher M.; Hehir, Ailish; Bekessy, Sarah A. (Taylor & Francis, 2017)
It is important for landscape planners and managers to understand how urban residents value and interact with green open spaces. However, the effect of spatial scale on values and perceptions of green open spaces has to date received little attention. This study explored the influence of spatial scale using Public Participation GIS (PPGIS) methods in the Lower Hunter region of Australia. By asking respondents to assign markers denoting various values and preferences to green spaces displayed on maps of their suburb and municipality, the influence of scale could be assessed experimentally. A greater abundance and diversity of value markers were consistently assigned at the suburb scale, yet this pattern was more pronounced for some values (e.g. physical activity) than others (e.g. nature, cultural significance). The strength of this relationship was related to socio-demographic variables such as education and income. These results have implications for understanding human-environment relationships and the use of PPGIS techniques to inform environmental planning.